A Study on Housing Affordability Problems Among Working Households in Phnom Penh, Cambodia - Menghoung, Seng; Noer, Melinda; Verinita, Verinita (Syntax Literate, 2025)
Phnom Penh’s housing affordability crisis, driven by rapid urbanization and income inequality, disproportionately affects working households, with 78.8% earning ≤ $1,200/month. This study identifies key affordability barriers and evaluates policy solutions to bridge the gap between income and housing costs. A quantitative survey of 151 households analyzed via descriptive statistics, factor analysis (KMO = 0.896), and PIR metrics. Five critical barriers emerged: policy gaps, financial constraints, market dynamics, limited awareness, and alternative preferences. The PIR revealed severe unaffordability (PIR > 5), with only homes priced ≤ $32,400 deemed accessible. Respondents strongly supported low-interest loans (<5%), affordable housing quotas (20%), and financial literacy programs. The study advocates for enforced policy interventions, developer mandates, and multi-sector collaboration, offering a replicable framework for rapidly urbanizing contexts. Findings align with global affordability strategies while addressing Cambodia-specific gaps in policy implementation and financial accessibility.